Using Images to Facilitate Writing for Skills Assessment: A Visual PELA - Baird, Craig; Dooey, Patricia (The Australian Journal of Indigenous Education, 2017)
Determining the writing skill level of students commencing tertiary education is a key element in predicting their likely study success and in providing appropriate writing development opportunities. Writing tests constructed around written instructions often assume high levels of reading and comprehension skills, which in some instances impose difficulties for students who have varying levels of comprehension and writing skills as shaped by their cultural and ethnic, learning journey experiences and previous formal English language instruction. Many universities have now established Post-Entry Language Assessment (PELA) tools as a means to determining student language skills at the commencement of their studies. Discussed here is a Visual PELA (VP) intended to stimulate student writing of a small passage of text for the purpose noted above. The visual nature of this instrument is intended to provide an alternative approach for visual learners, or those for whom written instructions pose difficulties, to demonstrate their literacy skills. This paper describes the development and initial testing of a VP with a view to it becoming an additional tool for determining writing skills levels for commencing students. A trial of this VP took place with a cohort of mostly international students having English as an Additional Language/Dialect (EAL/D) undertaking higher degree by research studies in an Australian university. The VP used here was founded on the idea of using images to stimulate the writing of a short passage of text where students can find their own context and ideas to write in an imaginative way and thus demonstrate their writing skill on entry to their tertiary studies.